Lecturer’s Nonverbal Communication attitude in Classroom: Its Meaning for College Sudent - Gofur; Muhlis; Rahmawati (ELITE JOURNAL, 2019)
The improvement of students interest and their willingness to study are mostly showed by their experience in the way of learning occurs. In this case the existence of the lecture’s role is very important as facilitator in the class with their good communication, not only transferring the knowledge but also provide a good classroom condition which drive the college students to get their knowledge. Off course this condition should provide them with a good communication skill. Well actually some of them in presenting t the learning process is done without an extensive preparation in the design. The objective of this research is improving the understanding of nonverbal communication attitude phenomenon in teaching learning process in order to improve the quality of it. With an ethnography studies used to reach the goal of the study. While the result shown that; 1) the lecturer applied several kind of nonverbal communication, 2)they face expression mostly with interpersonal relation between lecturer and the college students. 3) the college students have a various response relate with to the lecturer face and eye contact expression. 4) lecturers eyes contact expression indicates whereas he/she pays a good attention to his class or not. This is the meaning of a lecture’s nonverbal communication attitudes for the college student, to prepare them emotions condition in order to join the teaching learning process